Sistem Pendukung Keputusan Penentuan Golongan UKT Dengan Metode Naïve Bayes - Yanda Sepri Yanifal; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Single Tuition (UKT) is a new system for tuition fees in accordance with the Minister of Higher Education and Culture Regulation number 55 in 2013. UKT is also a form of cross-subsidy system whereas students with high economic levels will subsidize students with low economic levels. So, this condition will alleviate for underprivileged students’ in the cost constraints of continuing study in college. To determine the UKT class for students, so, UKT classes must be fit with the students’ economic level. Under these conditions, the author to make a Decision Support System (DSS) determines the class of student UKT by using the Naive Bayes Method. There are seven input variables of 600 students' data from University of Riau Academic Year 2014 to 2015 used in this study, consisting of 400 training data and 200 test data. This system is developed by using PHP Programming Language, Mysql and this system also Naive Bayes Method. This Method is used to classify data into six UKT groups. uses this method can provide the best alternative based on training from previous data, to determine a single tuition based on students' economic. Testing data results of this study indicate that Naive Bayes Method can identify students’ UKT groups with accuration average of 91.5% of 200 test data. So, it can be concluded that UKT effectiveness level with the Naive Bayes Method included in to Good Category.Keywords : Decision Support Systems, Naïve Bayes